Black Rangers, Enslaved Mobilities, and the Black Geography of Early Nineteenth-Century Grenada. - Freund, Heather (Slavery & Abolition, 2026)
Nineteenth-century Grenada was an island still recovering from Fedon's Rebellion (1795–1796), which nearly toppled British rule. In its aftermath, the colonial government maintained a standing body of enslaved troops to control enslaved mobility: the Loyal Black Rangers. Their activities reveal the need for a more nuanced understanding of enslaved movement in the Lesser Antilles. This article focuses on overland marronage, showing that many bondspeople sought freedom inland rather than across the sea or in the towns. It argues that enslaved movements were facilitated by the physical geography, plantation landscape, and demography of Grenada, but hampered by the pervasiveness of the Loyal Black Rangers. It intertwines an examination of enslaved people who fled bondage with that of the Rangers who hunted them, highlighting their shared understanding of Grenada's Black geography and the complexity of their relative positions within a slave society.